Redes de interação proteína- proteína em Ureaplasma Diversum: evidências de transferência horizontal de genes e da evolução dos genomas reduzidos na classe Mollicutes - Silva, Joana Maria Kastle (2018)
Proteins do not perform their biological functions alone and are instead connected in proteinprotein interaction networks. These networks provide the foundation for different metabolic pathways and cellular processes that guarantee cell survival and proliferation, as well as the colonization of novel niches. Ureaplasma diversum is a member of the Mollicute class and causes urogenital tract infections in cattle and small ruminants. As it is the rule among Mollicutes, U. diversum does not have a cellular wall and is characterized by a reduced genome and incomplete or completely lacking metabolic pathways. Studies indicate that the process of horizontal gene transfer, the exchange of genetic material among non-descendant individuals, has a crucial role in Mollicute evolution, affecting their genomic reduction process and the simplification of metabolic pathways. We constructed the protein-protein interaction network of U. diversum and compared it with the networks of other members of the Mollicute class and external groups to test if the reduction of complexity in this class is reflected in their protein interaction networks. We also investigated horizontal gene transfer events in sub-networks of interest involved in purine and pyrimidine metabolism (incomplete pathways in Ureaplasmas and Mycoplasmas) and urease function, an enzyme that supplies the energy demand in Ureaplasma and acts as a virulence factor. We identified horizontal gene transfer events among Mollicutes and from Ureaplasma to S. aureus and Corynebacterium, bacterial groups that colonize the urogenital niche. The overall tendency of genome reduction and simplification in the Mollicutes is reflected in their protein interaction networks, tending to be more generalistic and less “selective”. This suggests that the process was permitted (or enabled) by an increase in host dependence and the available gene repertoire in the urogenital tract via horizontal gene transfer.